FROM INFORMATION MANAGEMENT TO QUALITY: AN AUDIT PROCESS AND STANDARDIZATION FOR TAW COMPANY - Carvalho, Milena; Oliveira, Bruna; Martins, Susana (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The project that is presented took place within the curricular unit of The Final Project Seminar / Internship of the degree in Library and Information Science and Technologies (LIST) of ISCAP-P.